Recruitment of Civil Servants Following The State of Emergency at The Sawang Subdisdrict Office, North Aceh Regency - Ruwaida Ruwaida; Aiyub Aiyub; Muryali Muryali; Cut Sukmawati; Ferizaldi Ferizaldi (Sebatik, 2026)
This study aims to determine the recruitment process of civil servants and its impact on professionalism and transparency at the Sawang Sub-District Office in North Aceh Regency. The method used in this study is descriptive qualitative, with data collection techniques including interviews, observation, and documentation. The data obtained was then analyzed through data reduction, data presentation, and data verification. The results of the study show that the recruitment of civil servants after the military emergency at the Sawang Subdistrict Office was simple, quick, and tended to be closed because it was more influenced by the need to maintain socio-political stability, reconciliation, and the continuity of government in a post-conflict situation than by the strict application of merit principles, so that the process did not involve open selection or competency tests. This situation has impacted the professionalism of the State Civil Apparatus, which is not yet optimal, as well as low levels of transparency, because the recruitment process is based more on social and situational considerations during the transition period. When compared to the principle of meritocracy, this recruitment practice is not entirely appropriate because it does not place qualifications, competence, potential, performance, and integrity as the main criteria, even though it can be understood as an adaptive policy by local governments to maintain peace and ensure that public services continue to run.